2018
DOI: 10.1186/s40793-018-0335-x
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Arcticibacterium luteifluviistationis SM1504T, a cytophagaceae bacterium isolated from Arctic surface seawater

Abstract: Arcticibacterium luteifluviistationis SM1504T was isolated from Arctic surface seawater and classified as a novel genus of the phylum Bacteroides. To date, no Arcticibacterium genomes have been reported, their genomic compositions and metabolic features are still unknown. Here, we reported the complete genome sequence of A. luteifluviistationis SM1504T, which comprises 5,379,839 bp with an average GC content of 37.20%. Genes related to various stress (such as radiation, osmosis and antibiotics) resistance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The cold adaptation of Al AXEase is consistent with the growth characteristics of strain SM1504 T , suggesting that its structural and biochemical properties are optimized to low temperatures. Genomic analysis showed that this strain contains some genes encoding potential xylanases, arabinofuranosidases, and other xylan-degrading enzymes ( 26 ). Al AXEase could hydrolyze many kinds of acetylated monosaccharides and disaccharides as well as xylan, with acetylated xylopyranose as the optimal substrate, suggesting that Al AXEase is likely involved in xylan/xylooligosaccharide degradation together with other xylan-degrading enzymes to provide carbon source and energy for its source strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cold adaptation of Al AXEase is consistent with the growth characteristics of strain SM1504 T , suggesting that its structural and biochemical properties are optimized to low temperatures. Genomic analysis showed that this strain contains some genes encoding potential xylanases, arabinofuranosidases, and other xylan-degrading enzymes ( 26 ). Al AXEase could hydrolyze many kinds of acetylated monosaccharides and disaccharides as well as xylan, with acetylated xylopyranose as the optimal substrate, suggesting that Al AXEase is likely involved in xylan/xylooligosaccharide degradation together with other xylan-degrading enzymes to provide carbon source and energy for its source strain.…”
Section: Discussionmentioning
confidence: 99%
“…Arcticibacterium luteifluviistationis SM1504 T is a cold-adapted bacterium isolated from an Arctic surface seawater sample from King’s Fjord, Svalbard ( 25 , 26 ). Here, we identified and characterized a novel SGNH-type AcXE, Al AXEase, from strain SM1504 T , which, together with its homologs, represents a new SGNH-type CE family.…”
mentioning
confidence: 99%
“…Micrococcaceae is a sodium polyacrylate and plant growth-promoting bacterium that promotes plant growth and yield [23]. Cytophagaceae family is the largest Bacteroidetes phylum that consists of a large number of genera (>31) and species (>80) [24][25][26]. Cytophagaceae family member is characterized by predominant respiratory quinone MK-7, major polar lipid phosphatidylethanolamine, 40 mol%~50 mol% DNA G+C content and iso-C 15∶0 , C 16∶1ω5c , and summed feature 3 (C 16:1ω7c and/or C 16:1ω6c ) cellular fatty acids [25,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The advancement of sequencing technologies has improved our understanding of psychrophile biology. To date, a number of psychrophilic microbes, including bacteria and fungi, have been sequenced from both polar regions [ 2 , 12 ]. Recently, the whole genome of a few psychrophilic yeasts has been sequenced including Glaciozyma antarctica [ 10 ], Mrakia hoshinonis [ 13 ] and Candida psychrophile [ 14 ].…”
Section: Molecular Adaptationmentioning
confidence: 99%